CFD simulation and validation of self-cleaning on solar panel surfaces with superhydrophilic coating. Issue 1 (22nd August 2015) - Hu, Jin; Bodard, Nicolas; Sari, Osmann; Riffat, Saffa
Abstract: Solar panel conversion efficiency, typically in the twenty percent range, is reduced by dust, grime, pollen, and other particulates that accumulate on the solar panel. Cleaning dirty panels to maintain peak efficiency, which is especially hard to do for large solar-panel arrays. To develop a transparent, anti-soiling Nano-TiO2 coating to minimize the need for occasional cleaning is the purpose of this study. In our study, a 2D rainwater runoff model along tilted solar panel surface based on the Nusselt solution was established to have better understanding and predicting the behavior of runoff rain water, especially in contact with solar-panel surfaces with Nano-TiO2 coating. Our simulation results demonstrate that solar-panel surfaces with Nano-TiO2 coating create a superhydrophilic surface which cannot hold water, showing features of more pronounced in increasing runoff water film velocity comparing to the uncoated surfaces during raining event resulting in better effect of self-cleaning. Validation of our model was performed on titled solar panels for real time outdoor exposure testing in Switzerland. It is found that the dust particles are not easy to adhere to the coated surfaces of the slides comparing with uncoated surfaces, showing great potential for its use in harsh environmental conditions. This study suggests that superhydrophilic self-cleaning solar panel coating maximize energy collection and increases the solar panel's energy efficiency.